Counter-Terrorism Strategy in Indonesia: A Language Policy Perspective - Henry Tondo, Fanny (Religion, Culture, and State Journal, 2022)
In this digital era, it is very important to have various strategic policies to counter terrorism in many aspects, including from linguistic point of view. It is a fact that the world is multilingual and the multilingualism management constitutes a problem to be overcome (Calvet 1998), especially how to prevent the spirit of terrorism from affecting the language use of Indonesian multilingual communities. A language policy (Spolsky 2009) includes diverse domains such as education, family, government, etc. From some studies that I have done regarding language policy in Indonesia there has never been a policy related to how linguistic strategies to counter terrorism. Based on that condition, my study is very significant to give contribution for peace Indonesia. This study was done by using secondary and primary data. This paper tries to explain how is the strategy to overcome terrorism from lingusitic point of view. It seems that the language policy in Indonesia has not accommodated strategic steps how to linguistically deal with terrorism both in the regulatory aspects and at the level of implementation in the community so that it is necessary to immediately revise the existing language regulations both at national and local levels.